2013
DOI: 10.1371/journal.pone.0082076
|View full text |Cite
|
Sign up to set email alerts
|

Initial Cell Seeding Density Influences Pancreatic Endocrine Development During in vitro Differentiation of Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESCs) have the ability to form cells derived from all three germ layers, and as such have received significant attention as a possible source for insulin-secreting pancreatic beta-cells for diabetes treatment. While considerable advances have been made in generating hESC-derived insulin-producing cells, to date in vitro-derived glucose-responsive beta-cells have remained an elusive goal. With the objective of increasing the in vitro formation of pancreatic endocrine cells, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 43 publications
2
62
0
1
Order By: Relevance
“…4 Based on this timeline, and one of the presumed PAX4 targets being ARX, we performed infections of developing hESC cultures at day 11 with either control virus expressing enhanced green fluorescent protein (Ad eGFP) or PAX4 virus (Ad PAX4) at a multiplicity of infection (MOI) of 6 or 60 based on a day 11 cell density of 4.3 x 10 5 cells/cm. 2,4 By day 12, eGFP-positive cells were observed in the control group, and eGFP expression was maintained until day 21 (Fig. 1B).…”
Section: Adenoviral Gene Delivery Of Pax4 To Hescsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Based on this timeline, and one of the presumed PAX4 targets being ARX, we performed infections of developing hESC cultures at day 11 with either control virus expressing enhanced green fluorescent protein (Ad eGFP) or PAX4 virus (Ad PAX4) at a multiplicity of infection (MOI) of 6 or 60 based on a day 11 cell density of 4.3 x 10 5 cells/cm. 2,4 By day 12, eGFP-positive cells were observed in the control group, and eGFP expression was maintained until day 21 (Fig. 1B).…”
Section: Adenoviral Gene Delivery Of Pax4 To Hescsmentioning
confidence: 99%
“…2 The majority of in vitro hESC-derived pancreatic endocrine cells express multiple hormones within the same cell. [3][4][5][6][7][8] While these polyhormonal cells are a natural component of human development, [9][10][11] the eventual bias of these cells, which most notably co-express glucagon and insulin, is to an Ī±-cell fate. 3,[12][13][14] Therefore, new methods that shift the polyhormonal nature of cells away from a glucagon-positive lineage could significantly improve the generation of functional Ī²-cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Various protocols have been developed to generate DE in vitro by recapitulating in vivo embryogenesis, but their efficiency varies widely [6][7][8][9][10][11]. It has been reported that the initiating DE density is influential for the final differentiation yield [12]. In view of the variability in DE production outcomes, validation and improvement of these protocols are needed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that the capacity of PSCs to differentiate into pancreatic endocrine cells is highly affected by the seeding density of initial cultures. For example, Gage et al [47] demonstrated that high density hESCs led to remarkable increase in that rate of cell differentiation into PDX1-and NGN3-positive cells as compared to low density cultured cells. In contrast to PDX1, NGN3 expression is stimulated by a reduction in NOTCH signaling.…”
Section: Differentiation Into Pancreatic Progenitors and Endocrine Cellsmentioning
confidence: 99%